2001
DOI: 10.1093/molehr/7.5.425
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA content affects the fertilizability of human oocytes

Abstract: Mitochondrial DNA content varies considerably in oocytes, even when collected from the same patient. In the present study, real-time quantitative polymerase chain reaction analysis of 113 unfertilized oocytes obtained from 43 patients revealed an average of 193,000 (range: 20,000 to 598,000) mitochondrial genomes per cell. We compared several groups of oocytes to investigate the relationship between mitochondrial DNA content and fertilizability. The average mitochondrial DNA copy number was significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
319
6
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(357 citation statements)
references
References 24 publications
17
319
6
8
Order By: Relevance
“…With an average of 3.67 Â 10 5 mtDNAs per mammalian oocyte (Steuerwald et al, 2000;Reynier et al, 2001;Barritt et al, 2002;Chan et al, 2005;May-Panloup et al, 2005a, b;Santos et al, 2006), the estimated mtDNA content per salmon oocyte is approximately three to four orders of magnitude higher than that reported for mammals. This finding is in agreement with stereological analyses estimating the number of mitochondria in toad and frog oocytes, indicating the mitochondrial DNA content of external fertilizers to exceed that of mammalian oocytes by at least three orders of magnitude (Romek and Krzysztofowicz, 2005;Shoubridge and Wai, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…With an average of 3.67 Â 10 5 mtDNAs per mammalian oocyte (Steuerwald et al, 2000;Reynier et al, 2001;Barritt et al, 2002;Chan et al, 2005;May-Panloup et al, 2005a, b;Santos et al, 2006), the estimated mtDNA content per salmon oocyte is approximately three to four orders of magnitude higher than that reported for mammals. This finding is in agreement with stereological analyses estimating the number of mitochondria in toad and frog oocytes, indicating the mitochondrial DNA content of external fertilizers to exceed that of mammalian oocytes by at least three orders of magnitude (Romek and Krzysztofowicz, 2005;Shoubridge and Wai, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Gametes of mice were estimated to contain 10-75 and 1.6 Â 10 5 mtDNA molecules per single sperm and oocyte, respectively (Hecht et al, 1984;Shitara et al, 2000;Steuerwald et al, 2000). Human sperm were estimated to contain 1.4-6.8 molecules (MayPanloup et al, 2003;Amaral et al, 2007) and oocytes 1.93-7.95 Â 10 5 mtDNAs (Steuerwald et al, 2000;Reynier et al, 2001;Barritt et al, 2002;Chan et al, 2005;May-Panloup et al, 2005a;Santos et al, 2006). These estimates lead to ratios of 1:5.7 Â 10 5 -1:2.8 Â 10 4 of paternal-to-maternal mtDNA in human and 1:1.6 Â 10 4 -1:2.1 Â 10 3 in mouse zygotes if paternal mtDNA enters the egg upon fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, between 120 000 and 350 000 mitochondria have been estimated to occur in MII human oocytes (Jansen 2000b, Cummins 2002. However, when mtDNA copy numbers are determined by polymerase chain reaction methodology using probes for specific genes such as ATPase 6 (Van Blerkom 2004) or directed to specific sequences (Brenner 2004), the number of human mitochondrial genomes in MII oocytes from the same or different cohort(s) has been reported to differ by well over an order of magnitude, ranging from a low of approximately 20 000 to well over 800 000 , Steuerwald et al 2000, Reynier et al 2001, Barrit et al 2002, Van Blerkom 2004. If the current consensus that each oocyte mitochondrion contains a single genome is accurate (Cummins 2002), this rather astonishing and unexpected variation in mtDNA numbers between similarly appearing oocytes raises some fundamental questions about how competence may be determined well before fertilization.…”
Section: Mitochondria As Metabolic Forces In Early Developmentmentioning
confidence: 99%
“…If the current consensus that each oocyte mitochondrion contains a single genome is accurate (Cummins 2002), this rather astonishing and unexpected variation in mtDNA numbers between similarly appearing oocytes raises some fundamental questions about how competence may be determined well before fertilization. Reynier et al (2001) proposed that premature arrest of preovulatory meiotic maturation and fertilization failure after conventional IVF may be directly related to low mtDNA numbers, especially in the 20 000 to 60 000 range, if low copy numbers are associated with a reduced metabolic capacity. Van Blerkom et al (1995) measured net cytoplasmic ATP levels in cohorts of unfertilized and uninseminated MII human oocytes obtained from women undergoing IVF and GIFT procedures and reported that the ATP content of equivalently appearing oocytes could differ by an order of magnitude.…”
Section: Mitochondria As Metabolic Forces In Early Developmentmentioning
confidence: 99%
“…The number of mitochondria in an oocyte can be estimated by analysis of mtDNA copy number because oocytes contain only one to two mtDNA copies per mitochondrion (Pikó and Matsumoto 1976;Pikó and Taylor 1987;Jansen 2000;Santos et al 2006b;Jiao et al 2007;Chiaratti and Meirelles 2010). For successful early embryonic development, a species-specific minimum number of mitochondria appears to be required; for example, mouse oocytes are thought to require at least 50 000-200 000 mtDNA copies (Cao et al 2007;Cree et al 2008;Wai et al 2008Wai et al , 2010, whereas bovine, porcine and human oocytes have been reported to require between 100 000 and 700 000 mtDNA copies if they are to retain developmental competence (Steuerwald et al 2000;Reynier et al 2001;May-Panloup et al 2005a;Almeida-Santos et al 2006b;Spikings et al 2007;Zeng et al 2007). However, during early embryonic development, mtDNA replication is transiently arrested (St. John et al 2010) and therefore the mtDNA copy number either remains constant (e.g.…”
Section: Introductionmentioning
confidence: 99%